2011
DOI: 10.1016/j.ejmech.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

2,6-Bis-arylmethyloxy-5-hydroxychromones with antiviral activity against both hepatitis C virus (HCV) and SARS-associated coronavirus (SCV)

Abstract: In this study, as a bioisosteric alternative scaffold of the antiviral aryl diketoacids (ADKs), we used 5-hydroxychromone on which two arylmethyloxy substituents were installed. The 5-hydroxychromones (5b-5g) thus prepared showed anti-HCV activity and, depending on the aromatic substituents on the 2-arylmethyloxy moiety, some of the derivatives (5b-5f) were also active against SCV. In addition, unlike the ADKs which showed selective inhibition against the helicase activity of the SCV NTPase/helicase, the 5-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 15 publications
(8 reference statements)
0
46
0
Order By: Relevance
“…Based on their mechanisms of action, CoV helicase inhibitors can be broadly categorized into two groups. The first group includes bananins and 5-hydroxychromone derivatives, which inhibit the unwinding and ATPase activity of SARS-CoV helicase, resulting in inhibition of viral replication in vitro 153,154 . However, the toxicity resulting from the inhibition of cellular ATPases or kinases by these compounds has limited their development for human use.…”
Section: Protein Cage Nanoparticlesmentioning
confidence: 99%
“…Based on their mechanisms of action, CoV helicase inhibitors can be broadly categorized into two groups. The first group includes bananins and 5-hydroxychromone derivatives, which inhibit the unwinding and ATPase activity of SARS-CoV helicase, resulting in inhibition of viral replication in vitro 153,154 . However, the toxicity resulting from the inhibition of cellular ATPases or kinases by these compounds has limited their development for human use.…”
Section: Protein Cage Nanoparticlesmentioning
confidence: 99%
“…Other studies have previously identified potential inhibitors of nsp13. Some of these inhibitors interfere with the unwinding and ATPase activities of nsp13 (23,31,62). Such inhibitors may also interfere with the ATPase activity of cellular ATPase or kinases and affect cellular activities.…”
mentioning
confidence: 99%
“…10A) and the adamantine-derived bananins (Fig. 10B) have a direct effect on the NTPase activity although they are not nucleotide analogs (Kim et al, 2011;Tanner et al, 2005). While chromones were not characterized in detail, bananins seemed to specifically inhibit nucleic acid-stimulated NTPase activity in a non-competitive fashion.…”
Section: Nidovirus Helicases As Drug Targetsmentioning
confidence: 98%